MATEMATIKALÍQ HÁM KOMPYUTERLI MODELLESTIRIW TEXNOLOGIYASÍ BOYÍNSHA ILIMIY-METODIKALÍQ PIKIRLER - Muxiyatdinova, A. (SCIENCE and SOCIETY, 2021)
This article is analyzed the relevance of computer modeling technologies and scientific methodological concepts used in the modeling system.